2021
DOI: 10.2147/cmar.s320380
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic Value of Combined CA19-9 with Aspartate Aminotransferase to Lymphocyte Ratio in Patients with Intrahepatic Cholangiocarcinoma After Hepatectomy

Abstract: Purpose The prognosis of intrahepatic cholangiocarcinoma (ICC) patients after surgical resection remains poor. Effective prognostic biomarkers are expected to stratify ICC patients and optimize their treatment strategies. To investigate the prognostic value of carbohydrate antigen 19-9 (CA19-9), aspartate aminotransferase to lymphocyte ratio index (ALRI), and their combination (CAC) in predicting long-term outcomes in ICC patients after hepatectomy. Patients and Methods … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 49 publications
1
4
0
Order By: Relevance
“…Intrahepatic duct invasion is the cause of intrahepatic duct dilatation [15], and it is thus rational that the ability of the tumour to infiltrate this duct is correlated with a higher risk of MVI. While higher levels of specific tumour markers, including CEA, CA19-9, and AFP, have been linked to reductions in overall and progression-free survival, they have largely not been found to be associated with ICC patient MVI status [7,[16][17][18][19]. Consistently, we observed no relationship between tumour marker levels and MVI positivity.…”
Section: Discussionsupporting
confidence: 67%
See 1 more Smart Citation
“…Intrahepatic duct invasion is the cause of intrahepatic duct dilatation [15], and it is thus rational that the ability of the tumour to infiltrate this duct is correlated with a higher risk of MVI. While higher levels of specific tumour markers, including CEA, CA19-9, and AFP, have been linked to reductions in overall and progression-free survival, they have largely not been found to be associated with ICC patient MVI status [7,[16][17][18][19]. Consistently, we observed no relationship between tumour marker levels and MVI positivity.…”
Section: Discussionsupporting
confidence: 67%
“…While higher levels of specific tumour markers, including CEA, CA19-9, and AFP, have been linked to reductions in overall and progression-free survival, they have largely not been found to be associated with ICC patient MVI status [ 7 , 16 19 ]. Consistently, we observed no relationship between tumour marker levels and MVI positivity.…”
Section: Discussionmentioning
confidence: 99%
“…Qiu et al. suggested that incorporating serum CA19-9 to a clinical index showed better value in prognostic stratification than CA19-9 alone ( 34 ). Thus, we proposed a novel index by combination TBS (tumor morphology) and CA19-9 (tumor-specific biomarker), termed CTC grade, and investigated its utility in predicting ICC patient long-term outcomes.…”
Section: Discussionmentioning
confidence: 99%
“… 10 Currently, accumulating evidence has shown that inflammation‐based scores, such as systemic immune‐inflammation index (SII), platelet‐to‐lymphocyte ratio (PLR), neutrophil‐to‐lymphocyte ratio (NLR), lymphocyte‐to‐monocyte ratio (LMR), prognostic nutritional index (PNI), aspartate aminotransferase/platelet count ratio index (APRI), aspartate aminotransferase (AST) to neutrophil ratio index (ANRI), and AST to lymphocyte ratio index (ALRI) could be used as the prognostic markers for cholangiocarcinoma. 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 Gamma‐glutamyl transpeptidase (GGT) to albumin ratio (GAR) was a newly identified inflammation‐based score. Initially, GAR was pointed out to be useful for stratification of patients with chronic hepatitis B.…”
Section: Introductionmentioning
confidence: 99%